Moving beyond skills as a social and economic panacea - Keep, E; Mayhew, K (2010)
This article examines two inter-related issues. First, the tendency for UK skills policies to act as a substitute for other social and economic measures. Second, the problem of current conceptualisations of skills policy creating narrowly-drawn, technicist interventions that are frequently incommensurate with the scale of the problems which they purport to tackle. The article suggests that current policy formation processes, particularly in England, are being deployed in a manner that seeks to close off consideration of other potential avenues by which contemporary social and economic problems might be addressed. The case is made for a wider framing of both policy possibilities and avenues for relevant research to support such policy development. © The Author(s) 2010.